CRYPTO REMITTANCES AND EXCHANGE RATE VOLATILITY IN NIGERIA: ANALYZING THE DISPLACEMENT OF TRADITIONAL CROSS BORDER INFLOWS - Agbeyinka, Ibrahim Yinka (J-MACC : journal of management and accounting, 2026)
This Nigeria’s exchange rate volatility has intensified in recent years amid rising digital financial flows and weakening foreign reserves. This study investigates the extent to which crypto remittances, traditional remittance inflows, and foreign exchange reserves influence exchange rate volatility in Nigeria. Drawing on monthly macroeconomic data from 2015 to 2024, the research employs a quantitative ex post facto design and utilizes multiple linear regression analysis to explore relationships among the variables. Exchange rate volatility is measured as the monthly standard deviation of the NGN/USD rate, while remittance and reserve data are sourced from institutional databases including the World Bank, Central Bank of Nigeria. Despite theoretical expectations and supporting literature, the study finds that none of the three variables has a statistically significant effect on exchange rate volatility. Crypto remittances and traditional remittances exhibit negative but weak coefficients, while foreign reserves, though negatively signed, also lack statistical relevance. These findings suggest that Nigeria’s exchange rate dynamics may be more influenced by unobserved structural and speculative factors rather than direct capital inflows. The study recommends enhanced crypto transaction monitoring, reforms to lower formal remittance costs, and strategic reserve accumulation to restore confidence in monetary stability.